Water and health: From environmental pressures to integrated responses - Boelee, Eline; Geerling, Gertjan; van der Zaan, Bas; Blauw, Anouk; Vethaak, A. Dick (Acta tropica, 2019)
[Display omitted] •Water disperses plastics, chemical pollutants, pathogens, antimicrobial resistance.•Use of polluted water creates exposure routes to these substances.•Water management alters aquatic habitat and insect vector breeding.•Waterborne plastics may carry hazardous chemicals, pathogens, and disease-bearing insects or snails.•Integrated water management can reverse health hazards and reduce impacts. The water-related exposome is a significant determinant of human health. The disease burden through water results from water-associated communicable and non-communicable diseases and is influenced by water pollution with chemicals, solid waste (mainly plastics), pathogens, insects and other disease vectors. This paper analyses a range of water practitioner-driven health issues, including infectious diseases and chemical intoxication, using the conceptual framework of Drivers, Pressures, State, Impacts, and Responses (DPSIR), complemented with a selective literature review. Pressures in the environment result in changes in the State of the water body: chemical pollution, microbiological contamination and the presence of vectors. These and other health hazards affect the State of human health. The resulting Impacts in an exposed population or affected ecosystem, in turn incite Responses. Pathways from Drivers to Impacts are quite divergent for chemical pollution, microbiological contamination and the spread of antimicrobial resistance, in vectors of disease and for the combined effects of plastics. Potential Responses from the water sector, however, show remarkable similarities. Integrated water management interventions have the potential to address Drivers, Pressures, Impacts, and State of several health issues at the same time. Systematic and integrated planning and management of water resources, with an eye for human health, could contribute to reducing or preventing negative health impacts and enhancing the health benefits.